2015
DOI: 10.18632/oncotarget.5045
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide mediates hyperglycemia-induced invasive activity via ERK and p38 MAPK in human pancreatic cancer

Abstract: Diabetes mellitus and pancreatic cancer are intimately related, as approximately 85% of pancreatic cancer patients suffer from glucose intolerance or even diabetes. In this study, we evaluate the underlying mechanism by which hyperglycemia modulates the invasive potential of cancer cells and contributes to their enhanced metastatic behavior. Here we show that hyperglycemia increases the hydrogen peroxide (H2O2) concentration through up-regulation of manganese superoxide dismutase (SOD2) expression, which furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 42 publications
3
31
0
Order By: Relevance
“…We hypothesized that in the case of hyperglycemia complicated by neoplastic diseases, disease progression would be related to p38 MAPK signaling, including tumor cell proliferation and the EMT process. We found that HG promoted proliferation and enhanced invasiveness in pancreatic cancer cells, which was consistent with previous results [16, 17]. In addition, we discovered that HG induced p38 MAPK phosphorylation in pancreatic cancer cells, both in vitro and in vivo .…”
Section: Discussionsupporting
confidence: 92%
“…We hypothesized that in the case of hyperglycemia complicated by neoplastic diseases, disease progression would be related to p38 MAPK signaling, including tumor cell proliferation and the EMT process. We found that HG promoted proliferation and enhanced invasiveness in pancreatic cancer cells, which was consistent with previous results [16, 17]. In addition, we discovered that HG induced p38 MAPK phosphorylation in pancreatic cancer cells, both in vitro and in vivo .…”
Section: Discussionsupporting
confidence: 92%
“…Numerous studies have shown that specific molecules can affect the tumorigenesis, progression, incursion as well as migration of pancreatic cancer by participating in the regulation of JAK/STAT pathway . MAPKKK cascade is the key molecule in the MAPK pathway, and MAPK pathway can be incorporated to control cell propagation, invasion, migration, apoptosis, tumorigenesis, and progression of pancreatic tumor, as well as chemotherapy response and clinical outcomes . For the two drugs that were identified in our current study, no previous studies have identified their functions on cancer treatment.…”
Section: Discussionmentioning
confidence: 88%
“…[41][42][43][44] MAPKKK cascade is the key molecule in the MAPK pathway, and MAPK pathway can be incorporated to control cell propagation, invasion, migration, apoptosis, tumorigenesis, and progression of pancreatic tumor, as well as chemotherapy response and clinical outcomes. [45][46][47][48][49][50][51] For the two drugs that were identified in our current study, no previous studies have identified their functions on cancer treatment. These two drugs as the targeted agents for pancreatic cancer remain to be confirmed by further research as well as clinical trials.…”
Section: Discussionmentioning
confidence: 96%
“…Members of the MAPK family include extracellular signal-regulated kinase (ERK), c-jun NH-2 terminal kinase (JNK) and p38 MAPK. Our previous study demonstrated that a moderate amount of H 2 O 2 is able to promote pancreatic cancer invasion via the activation of the ERK and p38 MAPK signaling pathways (10). However, the ability of curcumin to inhibit the H 2 O 2 -induced progression of pancreatic cancer and the mechanisms related to this process have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, an excessive amount of ROS production can kill cancer cells, whereas sublethal concentrations of ROS can stimulate tumor progression by promoting cell proliferation, survival, invasion and metastasis (9). Additionally, our previous study showed that H 2 O 2 (0-200 µM) could promote pancreatic cancer progression in a dose-dependent manner, while H 2 O 2 was cytotoxic at concentrations above 200 µM (10). A recent study showed that curcumin possesses a protective effect against the epithelial-mesenchymal transition (EMT) process in the prostate tumor-stromal interaction, which is dependent on its ability to ameliorate cancer-associated fibroblast-induced ROS production through the MAOA/mTOR/HIF-1α signaling pathway (11).…”
Section: Introductionmentioning
confidence: 99%